Forgiveness as a protective factor among adolescents in bullying and cyberbullying contexts: Examining the impact on psychological adjustment - Quintana-Orts, Cirenia Luz (My University, 2019)
Recent studies have indicated that traditional bullying and cyberbullying are very damaging phenomena with considerable amounts of negative consequences for social, physical, and mental health in adolescence (Zych et al., 2015; Sigurdson et al., 2015). Traditionally, approaches towards bullying have focused on the mitigation of risk factors and the amelioration of the adolescents’ deficiencies that make them vulnerable to experience bullying (Hinduja & Patchin, 2017). From the Positive Psychology framework (Seligman & Csikszentmilhalyi, 2000), there is an interest on which protective factors could help adolescents to overcome the deleterious consequences of bullying, as well as equip them with health- protective skills that will help them to deal with stressful events and decrease the likelihood of engaging in aggressive behaviors such as traditional bullying and cyberbullying (Hinduja & Patchin, 2017; Kowalski et al., 2018). Based on this strength-oriented model, one promising personal resource that seems to protect individuals after interpersonal transgressions is forgiveness. According to this emerging field, forgiveness can be considered as a personal resource (Peterson & Seligman, 2004) that can be used as an emotion-focused coping (Worthington & Scherer, 2004) to manage the stressful and negative emotions, thoughts and behaviors associated to hurtful interpersonal transgressions. Prior research has demonstrated the protective role of forgiveness in adolescence. Beyond the general benefits of forgiveness in adolescents’ mental health, research findings have suggested that forgiveness might reduce violent behaviors and reactions associated with bullying (Peets et al., 2013; Van Rensburg & Raubenheimer, 2015), as well as it would help victims to alleviate the negative outcomes of being bullied (Egan & Todorov, 2009; Skaar et al., 2016).
El perdón como recurso protector de los adolescentes en contextos de acoso y ciberacoso: análisis de los efectos sobre indicadores de ajuste psicológico
However, in spite of the recent empirical evidence, the study of forgiveness is still relatively scarce. A better knowledge of forgiveness and its potential benefits for mental health would help to guide future research and to inform practical implications for adolescents and bullying prevention. Thus, the main purpose of this Thesis Dissertation was to extend the knowledge towards the associations between forgiveness, mental health, and both traditional bullying and cyberbullying in adolescence. FECHA DE LECTURA DE TESIS DOCTORAL: 17 de Septiembre de 2019.
Keywords: Acoso moral en la escuela - Tesis doctorales; Positive Psychology; Forgiveness; Bullying; Mental health; Adolescence